El principio de no discriminación contenido en la Decisión 578 de la Comunidad Andina de Naciones y las rentas de capital - Tartarini Tamburini, Tulio (2013)
Discrimination concerning taxpayers is often found in every tax system, which allows double tax burden to happen. It is for this reason that agreements such as the Double Taxation conventions and the Andean Community Resolution 578 arise, which refer to the non discrimination principle. In the following article, the author proposes a new way to interpret this non-discrimination principle contained in the Andean Community Resolution 578, analyzing Peru's context and legislation in order to determine how to solve this problem when, for example, there is a differentiated treatment and a consequent unfair taxation to those who domicile abroad.